The OHM Pays de Bitche as a testing ground for interdisciplinary and participatory scientific practice - Hein, Fabien (Comptes Rendus. Géoscience, 2024)
This article explores the process of implementing an interdisciplinary and participatory scientific approach in the “OHM Pays de Bitche” (Pays de Bitche Human-Environment Observatory).